Impact of changes in weight and haematocrit on the reduction in systolic office and ambulatory blood pressure with empagliflozin in patients with type 2 diabetes. (14th October 2021) - Sharma, A; Wanner, C; Ofstad, A P; Mattheus, M; Kraus, B J; Zinman, B; Ferreira, J P
Abstract: Background: There is uncertainty on how empagliflozin (EMPA) reduces blood pressure (BP), and in particular the potential role for changes in weight and haematocrit in mediating these effects. Purpose: To assess the contributions of changes in weight and haematocrit on EMPA induced changes in BP in patients with type 2 diabetes mellitus (T2DM) in the EMPA-BP and EMPA-REG OUTCOME trials. Methods: Patients received placebo (PBO), EMPA 10 mg or EMPA 25 mg. In EMPA-BP (12-week study), 823 patients with T2DM and hypertension (mean [SD] age 60.2 [9.0] years, HbA1c 7.90 [0.74] %, BMI 32.6 [5.1] kg/m 2 ) were studied. In EMPA-REG OUTCOME, of the 7, 020 treated patients with T2DM and cardiovascular disease (mean [SD] age 63.1 [8.6] years, HbA1c 8.07 [0.85] %, BMI 30.6 [5.3] kg/m 2 ), 95.0% were on anti-hypertensive treatment at baseline. ANCOVA/MMRM models were applied to assess changes in systolic BP (SBP) at week 12 associated with, and independent of, changes in weight and haematocrit (Hct). SBP measurements are based on mean 24-h measurements from an ambulatory blood pressure monitoring (ABPM) device in EMPA-BP and seated office measurements in EMPA-REG OUTCOME. Results: Mean (SD) baseline SBP was 131.7 (11.8), 131.3 (13.0) and 131.2 (12.1) mmHg in the PBO, EMPA 10 mg and EMPA 25 mg groups, respectively in EMPA-BP (mean 24-h SBP) and 135.8 (17.2), 134.9 (16.8) and 135.6 (17.0) mmHg (office SBP), respectively in EMPA-REG OUTCOME. In these relatively young patients with T2DM and mildly elevated mean SBP, EMPA reduced mean SBP by 3.4–4.2 mmHg compared with PBO (table) at week 12. Mean (SE) weight was reduced with EMPA (10 and 25mg) vs PBO treatment by −1.5 (0.2) kg and −2.0 (0.2) kg in EMPA-BP and by −1.2 (0.1) kg and −1.5 (0.1) kg in EMPA-REG OUTCOME at week 12. Mean (SE) haematocrit was increased by 2.1 (0.2) % and 1.8 (0.2) % versus placebo in EMPA-BP and by 2.2 (0.1) % and 2.5 (0.1) % in EMPA-REG OUTCOME with EMPA 10 mg and EMPA 25 mg, respectively. Weight loss accounted for 21–24% of the SBP reduction with EMPA treatment in EMPA-BP and 9–11% in EMPA-REG OUTCOME. Changes in Hct accounted for negligible (between −10% to 1%) SBP reduction with EMPA. Conclusion: The reduction in SBP is modestly mediated through a reduction in weight. There was no meaningful effect of EMPA induced changes in Hct on SBP. Results were consistent using ABPM or office SBP. These findings suggest that EMPA's effects on SBP are likely mediated through other mechanisms such as natriuresis or reduction in arterial stiffness. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boehringer Ingelheim and Eli Lilly and Company.